PENGARUH PENERAPAN SISTEM INFORMASI PENGELOLAAN KEUANGAN, PEMANFAATAN TEKNOLOGI DAN PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA PARIAMAN - Fikri, Ahmad; Multama, Ilham; Wahyuni EDT, Risa; Bur, Suhatri (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2024)
The purpose of this study is to analyze the effect of the implementation of financial management information systems, technology utilization and internal control on the quality of financial reports in the Pariaman City Government. Good financial report quality is very important for transparency and accountability in public financial management. This study uses variables of financial management information systems, technology utilization and internal control which are carried out to test their effect on the quality of financial reports of the Pariaman City Government. The process of data collection and sample determination uses the purposive sampling method, so that it is produced that by using this method 60 analysis samples are obtained consisting of 30 government agencies related to the OPD. The analysis method used is statistical analysis and is supported by using SPSS version 29. The statistical analysis method used is a descriptive analysis model and multiple linear regression analysis methods. The SIPD and Technology Utilization variables are tested partially which states that this variable has a significant effect on the Quality of Financial Reports while the Internal Control variable is tested partially which states that this variable does not affect the Quality of Financial Reports of the Pariaman City Government. Simultaneously, all independent variables, namely the financial management information system, technology utilization and internal control, have a joint effect on the quality of the Pariaman City Government's financial reports. The influence of the independent variable is 0.314 or 31.4% which can be seen in the value in this study.